2006
DOI: 10.1074/jbc.m607883200
|View full text |Cite
|
Sign up to set email alerts
|

Two Conserved Residues Govern the Salt and pH Dependencies of the Binding Reaction of a PDZ Domain

Abstract: PDZ domains are protein-protein interaction modules found in hundreds of human proteins. Their binding reactions are sensitive to variations in salt and pH but the basis of the respective dependence has not been clear. We investigated the binding reaction between PSD-95 PDZ3 and a peptide corresponding to a native ligand with protein engineering in conjunction with stopped-flow and equilibrium fluorimetry and found that the two conserved residues Arg-318 and His-372 were responsible for the salt and pH depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 33 publications
(51 reference statements)
1
57
0
Order By: Relevance
“…The PSD95 PDZ3 used in this study was similar to that in Chi et al (20). The numbering of residues in this article is in accordance with the crystal structure of PSD95 PDZ3 (13) (PDB entry 1BE9).…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…The PSD95 PDZ3 used in this study was similar to that in Chi et al (20). The numbering of residues in this article is in accordance with the crystal structure of PSD95 PDZ3 (13) (PDB entry 1BE9).…”
Section: Methodsmentioning
confidence: 83%
“…We chose to use the same reference mutation, H372Y, as in the previous study (7). The decrease in affinity for the H372Y mutation (two orders of magnitude) was similar to that for the deletion mutation H372A (20), suggesting that the hydrogen bond present in the wild-type complex (13) is not formed between the mutant H372Y and the peptide. It is clear that the PDZ domain pays a thermodynamic penalty for this functional His residue because mutation to either Ala or Tyr stabilizes the protein by Ϸ2 kcal⅐mol Ϫ1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…43) as well as a short His-tag, which does not influence the folding of PDZ3 (21). Expression and purification were as described earlier (37,46). The purity was checked by SDS/PAGE and the identity, by MALDI-TOF mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is well-documented that the binding affinity can also depend on the phosphorylation state of the target (Cohen et al, 1998;Chung et al, 2000;Hegedüs et al, 2003), as well as the conditions of the surrounding solution, such as the ionic strength, pH, and redox potential (Chi et al, 2006;Mishra et al, 2007). It was surprising when studies suggested that, in the canonical PDZ domain, residues away from the binding pocket can affect the binding affinity (Lockless and Ranganathan, 1999), because such residues were previously thought to have only a supporting structural role.…”
Section: Introductionmentioning
confidence: 99%